ANALYSIS OF STUDENTS’ PERCEPTION ON ONLINE SPEAKING LEARNING DURING COVID 19 - Habizar Habizar (Universitas Jambi, 2023)
This study aimed to know students’ perception on learning speaking via online such us zoom meeting etc., during the covid-19 pandemic. This study employed a quantitative research with used a survey method by using questionnaires to collect the data and SPSS to analyze the data from 51 respondents from one of university in Jambi. This research expected to be useful for students and other researchers. The questionnaire consists of six categories in this research. The result of this research showed that in the first category got three interpretations (High, Moderate, Low) for five total item. The scale of the item rangging from 2.88 to 3.76 means score. The second category got a moderate interpretation with the percentage 60% of the respondents chose neutral and 28% chose agree. The third and fourth category got high and moderate interpretation. The fifth and the last category got a moderate interpretation with the most of participants chose neutral. The result of the data analysis revealed that most of the students as the participants had a positive perception of learning speaking by virtual learning. Moreover the lack of internet connection should have accessible for them to get access on the internet. Beside that 34% of the respondents prefer to learning by offline learning (traditional learning).